2022
DOI: 10.1177/19458924221113124
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Olfactory Training in Post-COVID-19 Patients: A Multicenter Randomized Clinical Trial

Abstract: Background Olfactory dysfunction (OD)—including anosmia and hyposmia—is a common symptom of COVID-19. Previous studies have identified olfactory training (OT) as an important treatment for postinfectious OD; however, little is known about its benefits and optimizations after SARS-CoV-2 infection. Objective This study aimed to assess whether olfactory training performance can be optimized using more fragrances over a shorter period of time in patients with persistent OD after COVID-19. In addition, we determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…The strongest evidence for the treatment of COVID‐19 OD recommends olfactory training. 7 , 8 , 9 , 10 , 11 Other proposed therapies based on prepandemic evidence involve the use of topical intranasal medications 12 , 13 , 14 and oral anti‐inflammatory/neuroprotective agents. 15 , 16 , 17 , 18 However, the efficacy remains moderate at best among all current proposed therapeutics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strongest evidence for the treatment of COVID‐19 OD recommends olfactory training. 7 , 8 , 9 , 10 , 11 Other proposed therapies based on prepandemic evidence involve the use of topical intranasal medications 12 , 13 , 14 and oral anti‐inflammatory/neuroprotective agents. 15 , 16 , 17 , 18 However, the efficacy remains moderate at best among all current proposed therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…While a Cochrane review last updated in December 2020 found no definitive treatments for persistent COVID‐19 OD, 6 there are multiple ongoing clinical trials and a few recently published studies. The strongest evidence for the treatment of COVID‐19 OD recommends olfactory training 7–11 . Other proposed therapies based on prepandemic evidence involve the use of topical intranasal medications 12–14 and oral anti‐inflammatory/neuroprotective agents 15–18 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, olfactory training has been proven to be helpful in postinfectious olfactory loss and can induce neural reorganization processes [ 68 , 69 , 70 , 71 ]. Research on treatment options for chemosensory dysfunction in the context of SARS-CoV-2 is growing [ 19 , 72 , 73 ] and will become more and more important in lessening the impact of long-COVID.…”
Section: Discussionmentioning
confidence: 99%
“…This study 1 joins several other recently published studies investigating the use of OT for COVID-19 olfactory dysfunction. [4][5][6] While evidence exists to support OT in non-COVID-19 postviral olfactory loss, 7 its efficacy in COVID-19-related chemosensory dysfunction is less obvious. While 1 study found a clinically meaningful improvement with OT, 4 the results were equivocal in another.…”
mentioning
confidence: 99%